(untitled) (Research, Society and Development, 2020)
The pathogenesis of COVID-19 is largely unknown, and data are limited on the clinical characteristics of patients and their prognostic factors, assuming that smoking is possibly associated with the adverse prognosis of the disease. This paper aims to describe, based on the scientific literature, the association between tobacco consumption and the progression of COVID-19. It is an integrative literature review, and searches were carried out in the PUBMED and BIREME database, using the descriptors “tobacco” and “COVID-19”, complete and free articles published in the year 2020. The final sample of this The review consisted of 8 (eight) scientific articles. The main changes related to the progression of COVID-19 in smokers in the studies analyzed were: greater expression of the ACE2 receptor gene in smokers, contributing to the progression of symptoms, increased inflammatory response in subchronic smokers of electronic cigarettes, enrichment the androgenic pathway and the specific positive regulation of the regulatory genes of the central pathway and the realization of campaigns to combat smoking. As long as the related pathophysiological processes are not fully elucidated, it is important to reinforce campaigns to maintain healthy lifestyle habits, among which the non-use of tobacco, even in alternative forms, such as electronic cigarettes, as use is associated with greater predisposition to more severe clinical manifestations of the disease.